Retrieval of Separated NiTi Instrument in Severe Curved Canal using an Ultrasonic Device: A Case Report - Putranto, Aditya W.; Maharti, Ike D.; Megantoro, Aryo; Ricardo, Shalina (Journal of Dentistry Indonesia, 2018)
Objective: We describe how to assess the degree of canal curvature and manage a separated instrument using an ultrasonic device. Case Report: A 24-year-old female was referred by a general dentist for an accidentally separated Protaper F2 instrument. The mesiobuccal canal was enlarged and the separated instrument could be visualized via the dental operating microscope. Preoperative radiography revealed a separated endodontic instrument at the middle to apical third of the mesiobuccal canal. Mesiobuccal canal curvature measured 66°. After rubber dam isolation, a specific ultrasonic tip and the dental operating microscope were used to gain access around the separated instrument until it loosened. The separated instrument was agitated and accidentally sucked into the high-speed suction device. The canal was evaluated with higher magnification via the dental operating microscope and postoperative radiographs were taken to confirm removal. Conclusion: Retrieval of a separated instrument in the curved canal is effective using a specific ultrasonic device plus a dental operating microscope